Field notes contributed by Thomas J. Staudt, fall 1986 - Staudt, Thomas J.et al (1986)
List of birds and locations contributed by Thomas J. Staudt with observers James L. Fuller, Thomas H. Kent and W. Ross Silcock. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed